Quantitative comparison of novel GCaMP-type genetically encoded Ca2+ indicators in mammalian neurons - Yamada, Yoshiyuki; Mikoshiba, Katsuhiko (Frontiers in Cellular Neuroscience, 2012)
New variants of GCaMP-type genetically encoded Ca2+ indicators (GECIs) have been continuously developed and heavily used in many areas of biology including neuroscience. The latest subfamily called “GECOs” were developed with in vitro high-throughput screening, and shown to have novel spectral properties and/or improved fluorescent responses over their ancestor GCaMP3. The most critical parameter in evaluating performance in neurons, however, remains uncharacterized: the relationship between the GECI responses and the number of action potentials (APs). Here we analyzed the GECI responses to APs in cortical pyramidal cells of mouse acute brain slices. Unexpectedly, we found that none of the GECOs exhibited any improved performance over GCaMP3. Our results imply that careful validation is required for the accurate prediction of the actual performance of GECIs in mammalian neurons. We propose that appropriate guidelines for evaluating their efficacy should be established for the benefit of research community, given the rapidly expanding use of GECIs in neuroscience.